Rosuvastatin reduces vascular inflammation and T cell and monocyte activation in HIV-infected subjects on antiretroviral therapy - Funderburg, Nicholas T. (J Acquir Immune Defic Syndr, 2015)
BACKGROUND: Despite suppressive antiretroviral therapy (ART), increased levels of immune activation persist in HIV-infected subjects. Statins have anti-inflammatory effects and may reduce immune activation in HIV disease. METHODS: SATURN-HIV is a randomized, double-blind, placebo-controlled trial assessing the effect of rosuvastatin (10mg/daily) on markers of cardiovascular risk and immune activation in ART-treated patients. T cell activation was measured by expression of CD38, HLA-DR, and PD1. Monocyte activation was measured with soluble markers (sCD14 and sCD163) and by enumeration of monocyte subpopulations and tissue factor (TF) expression. Markers of systemic and vascular inflammation and coagulation were also measured. SATURN-HIV is registered on clinicaltrials.gov, Identifier: NCT01218802 RESULTS: Rosuvastatin, compared to placebo, reduced sCD14 (−10.4% vs 0.5%p=0.006), Lp-PLA(2) (−12.2% vs −1.7% p=0.0007), and IP-10 (−27.5 vs −8.2%, p=0.03) levels after 48 weeks. The proportion of TF+ patrolling (CD14(Dim)CD16+) monocytes was also reduced by rosuvastatin (−41.6%) compared to the placebo (−18.8%, p=0.005). There was also a greater decrease in the proportions of activated (CD38+HLA-DR+) T cells between the arms (−38.1% vs −17.8%, p=0.009 for CD4+ cells and −44.8% vs −27.4%, p=0.003 for CD8+ cells). CONCLUSIONS: 48 weeks of rosuvastatin treatment reduced significantly several markers of inflammation and lymphocyte and monocyte activation in ART-treated subjects.